Molecular Decoration and Unconventional Double Bond Migration in Irumamycin Biosynthesis - Vera A. Alferova; Anna A. Baranova; Olga A. Belozerova; Evgeny L. Gulyak; Andrey A. Mikhaylov; Yaroslav V. Solovev; Mikhail Y. Zhitlov; Arseniy A. Sinichich; Anton P. Tyurin; Ekaterina A. Trusova; Alexey V. Beletsky; Andrey V. Mardanov; et al. (Antibiotics)
Irumamycin (Iru) is a complex polyketide with pronounced antifungal activity produced by a type I polyketide (PKS) synthase. Iru features a unique hemiketal ring and an epoxide group, making its biosynthesis and the structural diversity of related compounds particularly intriguing. In this study, we performed a detailed analysis of the iru biosynthetic gene cluster (BGC) to uncover the mechanisms underlying Iru formation. We examined the iru PKS, including the domain architecture of individual modules and the overall spatial structure of the PKS, and uncovered discrepancies in substrate specificity and iterative chain elongation. Two potential pathways for the formation of the hemiketal ring, involving either an olefin shift or electrocyclization, were proposed and assessed using 18O-labeling experiments and reaction activation energy calculations. Based on our findings, the hemiketal ring is likely formed by PKS-assisted double bond migration and TE domain-mediated cyclization. Furthermore, putative tailoring enzymes mediating epoxide formation specific to Iru were identified. The revealed Iru biosynthetic machinery provides insight into the complex enzymatic processes involved in Iru production, including macrocycle sculpting and decoration. These mechanistic details open new avenues for a targeted architecture of novel macrolide analogs through synthetic biology and biosynthetic engineering.